1958
DOI: 10.1515/znb-1958-0910
|View full text |Cite
|
Sign up to set email alerts
|

Über ernährungsphysiologische Veränderungen der Milch beim technischen Trocknen

Abstract: Der von uns entdeckte Effekt, daß zwischen Magermilchpulver und frischer Magermilch ein ganz eindeutiger, ernährungsphysiologischer Unterschied bezüglich der Auslösung von alimentärer Lebernekrose bei jungen Albinoratten besteht, wurde in mehrjährigen Untersuchungen1 immer wieder bestätigt gefunden.Die Versuchsergebnisse werden in Übersichtstabellen erstmals bekannt gegeben.Bisher wurden, zugleich zum Studium verschiedener spezieller Fragestellungen und Versuchsvarianten, sechzig handelsüblich hergestellte Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1960
1960
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This suggests the possible formation of some inhibitory or antinutritional compounds during Maillard reaction, the presence of which cannot be detected with short-term nutritional assays. Moreover, the short-term feeding effects reported in the literature (Fink et al, 1958;Adrian, 1974) seem to be due in part to nutritional deficiency and not specifically the browning compounds. Furthermore, there are no reports concerning the effects of long-term feeding of brown compounds available in the literature.…”
mentioning
confidence: 97%
“…This suggests the possible formation of some inhibitory or antinutritional compounds during Maillard reaction, the presence of which cannot be detected with short-term nutritional assays. Moreover, the short-term feeding effects reported in the literature (Fink et al, 1958;Adrian, 1974) seem to be due in part to nutritional deficiency and not specifically the browning compounds. Furthermore, there are no reports concerning the effects of long-term feeding of brown compounds available in the literature.…”
mentioning
confidence: 97%
“…The addition of the anti-oxidants, propyl gallate and butylhydroxyanisole, has no effect on the rate of tocopherol loss during storage or heating (123). The same workers (124) have also suggested that the tocopherol content of ghee might be used as an index of adulteration. Normal ghee was found to contain between about 20 and 45 fig tocopherol/g and the method enables adulteration above about 10% to be detected.…”
Section: (C) Vitamin Ementioning
confidence: 99%
“…During the last few years Fink and his collaborators have reported a series of experiments which demonstrated that a large proportion of samples of roller-dried skim-milk, and some spray-dried powders, caused liver necrosis in rats under conditions in which fresh milk did not (119,120,121,122,123,124). The albino rats used in these experiments received a diet containing 10 % of milk protein which constituted over 90 % of the protein of the diet and they remained on the experimental diet for up to 120 days.…”
Section: Selenium and The Necrogenic Properties Of Dried Skim-milkmentioning
confidence: 99%